[Documents relating to the closure of the Society] - Society for Promoting Female Education in China, India, and the East Committee; Church Missionary Society; University of Birmingham; Adam Matthew Digital (Adam Matthew Digital, 1899)
Typescript circular (May 30, 1899) and ms. letter (July 15, 1899) from Committee members of the Female Education Society recommending and announcing the decision to discontinue the Society's activities in China, Japan, India and other missions; and a letter from the Committee of the Church Missionary Society offering a mission posting to a former Female Education Society missionary (Aug. 3, 1899)